The Influence of Broadcast Program Quality, Announcer Credibility, and Broadcast Interactivity on Listener Loyalty of RRI Bandar Lampung - Argha Wijaya; Rahyono; Ayu Nursari (Yayasan Multidimensi Kreatif, 2026)
The development of digital media has driven significant changes in people's media consumption patterns, thus requiring radio stations to adapt in order to maintain the loyalty of their listeners. Radio Republik Indonesia (RRI) as a public broadcasting institution faces challenges in maintaining the existence and attachment of audiences in the midst of competition with digital media. This study aims to analyze the influence of broadcast program quality, broadcaster credibility, and broadcast interactivity on the loyalty of RRI Bandar Lampung listeners, both partially and simultaneously. This study uses a quantitative approach with a survey method. Primary data was collected through the distribution of a Likert scale questionnaire to active listeners of RRI Bandar Lampung who were selected using certain sampling techniques. The data analysis was carried out using multiple linear regression, and was supported by validity, reliability, and classical assumption tests. The results of the study show that partially the quality of broadcast programs, the credibility of broadcasters, and broadcast interactivity have a positive and significant effect on the loyalty of RRI Bandar Lampung listeners. In addition, the results of the simultaneous test showed that the three independent variables together had a significant effect on listener loyalty. These findings confirm that improving the quality of broadcast programs, strengthening broadcasters' credibility, and optimizing broadcast interactivity are important factors in building and maintaining listener loyalty. This research is expected to make a theoretical contribution to the development of broadcast communication studies, as well as become a practical consideration for the management of RRI Bandar Lampung in designing a broadcast management strategy oriented towards audience loyalty.